Low-temperature electrical discharge through solid xenon - Gordon, E.B.; Matyushenko, V.I.; Sizov, V.D.; Smirnov, B.M. (Физика низких температур, 2008)
The uniform self-sustained electrical discharge through solid xenon has been realized and studied. The
multiplication of electrons proceeds in the noble gas above the xenon crystal interface whereas a positive
feedback is realized at the account of multiple exciton formation by excess electrons drifted through the
crystal: molecular excitons emit VUV photons which knocked out secondary electrons from photosensitive
cathode. The discharge was stimulated by short electrical spark along the sample axes. The discharge electrical
properties as well as the spectra of solid xenon electroluminescence in UV and visible have been studied.
Electric discharge in solid xenon was proved to be an effective source of UV radiation and a convenient tool
to study the processes involving excitons and electrons in solid xenon at high pressures.